Decoupling highly structured polynomial systems. (March 2017) - Bates, Daniel J.; Newell, Andrew J.; Niemerg, Matthew E.
Abstract: An efficient technique for finding numerical approximations of isolated solutions of polynomial systems with a particular structure is presented. This structure is quite specific but arises naturally, for example when computing the critical points of a symmetric polynomial energy function. An illustrative example from magnetism is presented, along with some timing comparisons.